Cost, benefit, and financial risk (COBEFR) of ERP implementation - Badewi, Amgad; Shehab, Essam (Cranfield University Press, 2013)
The purpose of this research is to develop Benefits, Costs, and Financial Risks (CoBeFR) model to show and measure the impact of ERP related decisions, such as degree of business process re-engineering and the level of hardware investment, on the organisational financial value (OFV). OFV is based on current time value of money (i.e. interest rate), financial risk, and net cash flows emerged from ERP system. Financial risk, the sensitivity of the organisation net profit to changes in market conditions, is affected by organisational adoption of ERP system. The main conclusion is that there are interrelated impacts of ERP implementation decisions to the organisational financial value. Therefore, decision maker should look at the implementation decision from a new perspective which is Organisational Financial Value (OFV) perspective
Keywords: ERP; Cost; Benefit; Financial Risks